ANALISIS KESIAPAN MENERAPKAN INTEGRATED REPORTING PADA INDEKS LQ-45 - Adriana Adriana (Master in Accounting Program, 2014)
This study provides an analysis related to the appropriateness of annual reports of companies registered at LQ-45 index compared to <IR> Framework. It aims to identify the readiness of the companies to apply integrated reporting. Elements needed to develop further will be also identified. Total of 76 questions are used in this study and referred to Berndt et al. (2014). Secondary data are obtained from annual reports of public companies in 2013 and included in the LQ-45 index per February-July 2014.The results of this study indicate that about 62,22% of companies are quite ready to apply integrated reporting. These companies have the average level of integrated reporting according to <IR> Framework. It also reflects the potency to develop the current reporting. In addition, companies require to evaluate their reporting such as: (1) business model; (2) governance; (3) basis of preparation & presentation and (4) strategy & resource allocation.On the basis of this study, 5 companies are recommended to consider integrated reporting as their reporting model in the future. The companies are SMGR, BMRI, PTBA, ADRO dan BBNI with the highest accodance to <IR> Framework. Those companies also need to consider principles of materiality and conciseness. Other issues can be prioritized to apply integrated reporting include financial and mining sectors.This study gives the understanding of the importance of integrated reporting as corporate reporting model. It can be considered for public companies in Indonesia to apply integrated reporting. Lastly, it can contribute to the development of integrated reporting in Indonesia